Gender Differences in Educational Attainment: The Evidence from the European Union Countries - Głodowska, Agnieszka Elżbieta (Horyzonty Wychowania, 2019)
RESEARCH OBJECTIVE: The aim of the article is to present the results of the analysis on diversity of the education attainment of women and men in the European Union countries. By implementing such a purpose, it is possible to present not only heterogeneity in education on the basis of gender but also disproportions between individual EU countries.THE RESEARCH PROBLEM AND METHODS: The article raises three important research problems: education, gender equality and diversification within the European Union countries. The analysis covers 28 EU countries and a period of 10 years: 2007 - 2016. The research method used in the paper is the analysis and criticism of the literature and taxonomic analysis using a set of diagnostic variables describing selected aspects of education.THE PROCESS OF ARGUMENTATION: The line of reasoning consists of three essential elements. The first part presents the problem of education with particular emphasis on gender gap according to international literature on the subject. The second part contains description of the research tools and methods. Part three of the article presents the results of the comparative study in the field of education of woman and man in the European Union members.RESEARCH RESULTS: The research results are consistent with previous studies indicating that the level of education of women is higher than that of men. The level of diversity of education of women and men in individual EU countries is moderate. Among the most educated economies, the Scandinavian countries should be indicated. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: This type of research can have significant useful value for shaping the education policy of women and men and other development policies. Considering the importance of education of women and men, there are definitely more possibilities of confronting the results of research with various areas of the economy.